Peran Umpan Balik Guru Dalam Meningkatkan Keterampilan Menulis Siswa - Anita Candra Dewi (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2025)
Writing skills are a crucial aspect of language acquisition, contributing to the development of students' critical, creative, and communicative thinking skills. However, various studies have shown that students' writing skills at various levels of education remain low. One key factor that can help improve the quality of students' writing is teacher feedback. This article aims to systematically review various studies that discuss the role of teacher feedback in improving students' writing skills. The method used is a literature study by analyzing national and international scientific articles published between 2019 and 2024 that are relevant to the research theme. The results of the study indicate that formative, constructive, and ongoing teacher feedback has been proven to improve the quality of students' writing, particularly in the aspects of idea organization, grammar, and vocabulary. Furthermore, the combination of direct and indirect feedback is considered effective in encouraging students' independent learning. Feedback provided through digital media also broadens the scope of communication and accelerates the writing revision process. In conclusion, the role of teachers in providing feedback is not only as evaluators but also as facilitators of writing learning, motivating and guiding students to produce better written work.